METHODOLOGY OF TECHNOLOGICAL EXPERIMENT RESULTS STATISTICAL EVALUATION IN FERROUS METALLURGY IN COMPUTING ENVIRONMENT OF STATISTICA AND MathCAD - Bytkin, Sergey; Krytskaya, Tatiana (Scientific Journal "Metallurgy", 2021)
To solve problems related to data analysis in the presence of random and / or unpredictable(unknown) factors (for example, different chemical composition of an array of metal melting dataand the results of one experimental melt in the presence of a small variational series ofmeasurements, stochastic, probabilistic methods are used. It make it possible to identifypatterns against the background technological deviations (the mechanical properties of thesamples, on which, for example, the yield point was measured, are associated not only with thechemical composition, but also with thermomechanical effects during rolling), make reasonableconclusions and predictions, give estimates of the probabilities of the numerical values of anyother physical quantities by comparing not the individual numerical values of the characteristicsof rolled metal, but their probabilities. The purpose of the present work was confirming the possibilityof the STATISTICA, MathCAD applied packages use for the effectiveness confirmation ofthe application of the new technological solution (deoxidation using ferrosilicoaluminum, FSA).As an example, a statistical analysis of experimental data on experimental 09G2D melting considered.The distribution of the yield point σТ for specimens made from standard 09G2D, as wellas the distribution of the yield stress for specimens made from experimental steel 09G2D isinvestigated. Histograms (STATISTICA) describing the distribution of the standard technologyσТ and the same when using technology with FSA were approximated by the probability densitydistribution function of the numerical value of the feature. The resulting distributions wereconstructed in the MathCAD with a simultaneous transition to the probabilistic representation ofdependencies. It was shown that the main effect of FSA use was the decrease of the σТdispersion of steel 09G2D.